polo, a mitotic mutant of Drosophila displaying abnormal spindle poles. - Sunkel, C.E.; Glover, D.M. (Journal of Cell Science, 1988)
Neuroblast cells in larvae homozygous for mutant alleles of the locus polo show a high frequency of metaphases in which the chromosomes have a circular arrangement, and anaphase figures in which chromosomes appear to be randomly oriented with respect to at least one of the spindle poles. These defects appear to lead to the production of polyploid cells. Sex chromosome disjunction is affected in male meiosis, primarily in the second division, and the meiotic spindles of living cells are abnormal. One allele is a larval lethal, whereas another is semi-lethal with about 7% of homozygotes surviving as adults. Embryos from homozygous polo females have aberrant mitotic spindles that are highly branched and have broad poles. Immunofluorescence studies with an antibody that recognizes an antigen associated with the centrosome indicate that the organization of this organelle is disrupted in the mutant embryos.